Ovarian cancer embryonic - Alcántara Ascón, René Augusto (2015)
From 1965 to 1990 are studied 33 cases of ovarian embryonary cancer at Belen and Regional hospitals of Trujillo, with the purpose of the find its frecuency and complications. These tumors represented the 17,6% of all malignant ovarian neoplasms, and the more frequent was the dysgerminoma (16 cases). There was more frequency in patients below 30 years old (29 cases), with pain and abdominal tumor (33 cases) and whose evolution were less than 7 months. By the other hand, 23 were in "stages III and V". All patients were operated except one woman who get death the day that was admitted at the hospital. Anemia were present in 15 cases and one of them had colonic perforation. Twenty five patients were translated to the Neoplasic Disease National Institute, 6 didn't return for their control, and 2 died because of the illness.